2021
DOI: 10.1002/anie.202112382
|View full text |Cite
|
Sign up to set email alerts
|

Fire‐Retardant, Stable‐Cycling and High‐Safety Sodium Ion Battery

Abstract: The safety of energy storage equipment has always been a stumbling block to the development of battery, and sodium ion battery is no exception. However, as an ultimate solution, the use of non‐flammable electrolyte is susceptible to the side effects, and its poor compatibility with electrode, causing failure of batteries. Here, we report a non‐flammable electrolyte design to achieve high‐performance sodium ion battery, which resolves the dilemma via regulating the solvation structure of electrolyte by hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…This suggests that the FDMA : MTFE system not only exhibits a low solubility of polar NaPSs to suppress their shuttling, [14] but also possesses weak dissociation of Na salts, allowing more anions to participate in SEI construction and thus, optimizing the electrode j electrolyte interfaces (insets of Figure 1d). [15] Molecular dynamics (MD) simulations were conducted to compare the solvation structures of three electrolytes: 1 M sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) -FDMA, 1 M NaTFSI-FDMA with 1 wt % FEC, and 1 M NaTFSI-FDMA : MTFE (1 : 1 by volume) with 1 wt % FEC electrolytes. The radial distribution functions (RDF) data and MD snapshot revealed that 1 M NaTFSI-FDMA electrolyte displayed a characteristic contact-ion pair-rich structure (CIP, one TFSI À coordinating to one Na + ) (Figure S2a), where 2.67 FDMA and 0.96 TFSI À coordinating to one Na + (Figure S2b), demonstrating the weakly solvating FDMA solvent allowed a participation of TFSI À in the solvation sheath of Na + .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the FDMA : MTFE system not only exhibits a low solubility of polar NaPSs to suppress their shuttling, [14] but also possesses weak dissociation of Na salts, allowing more anions to participate in SEI construction and thus, optimizing the electrode j electrolyte interfaces (insets of Figure 1d). [15] Molecular dynamics (MD) simulations were conducted to compare the solvation structures of three electrolytes: 1 M sodium bis(trifluoromethylsulfonyl)imide (NaTFSI) -FDMA, 1 M NaTFSI-FDMA with 1 wt % FEC, and 1 M NaTFSI-FDMA : MTFE (1 : 1 by volume) with 1 wt % FEC electrolytes. The radial distribution functions (RDF) data and MD snapshot revealed that 1 M NaTFSI-FDMA electrolyte displayed a characteristic contact-ion pair-rich structure (CIP, one TFSI À coordinating to one Na + ) (Figure S2a), where 2.67 FDMA and 0.96 TFSI À coordinating to one Na + (Figure S2b), demonstrating the weakly solvating FDMA solvent allowed a participation of TFSI À in the solvation sheath of Na + .…”
Section: Resultsmentioning
confidence: 99%
“…To date, the most used electrolyte are liquid electrolytes, they show the merits of high ionic conductivity and low resistance for high energy cells, but the potential risks of electrolyte leakage and flammability can't be ignored during application. [ 186 ] To solve these challenges and further improve the energy density of full cells, more and more attention has been paid to constructing solid‐state electrolytes, especially the polymer gel electrolyte composed of liquid electrolyte and the hosting polymer networks. [ 215 ] The preparation process is facile, while most of the organic, aqueous, and ionic liquid electrolytes can be used in this system.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced with permission. [ 186 ] Copyright 2021, WILEY‐VCH. e) Cycling performance of full cells at different being states.…”
Section: Sodium‐ion Full Batteriesmentioning
confidence: 99%
See 2 more Smart Citations